PENGARUH KONSENTRASI PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERUNG PADA TANAH ALUVIAL - Lestari, Sri; Zulfita, Dwi; Maulidi, Maulidi (Jurnal Sains Pertanian Equator, 2014)
This research aimed to know the effect of the concentration of liquid organic seedto the growth and result of eegplant on alluvial soil. The research uses acompletely randomized design (CRD) the consint of 5 treatments and eachtreatments is repeated 5 times and replication consint of 3 plant samples. Thetreatment consist of POC 0,2 % (A), POC 0,3 % (B), 0,4 % (C), 0,5 % (D), 0,6 %(E). Observed variabels in this research are plant dry weight (g), days toflowering (HST), the number of flower each plant (bud), flower become fruitpercentege (%), number of fruits each plant (fruit), fruit weight each plant (g),number of fruit each plot (fruit). The results of this research shows the treatmeantgives significant effect on all the research variables. Concentration of 0,2 % produces the best growth and result to the variable plant dry weight, percentageof flowers into fruits, the number of fruits each plant, the number of number offruit each plot and fruit weight.Keywords: Concentration, Liquid Organic Seed (LOS), Eggplant, Alluvial soil